Regional specifics of Macedonian agriculture - Anakiev, Boris; Kabranova, Romina; Arsov, Zlatko (Economics of Agriculture, 2010)
Macedonia is located on the Southern Continental layer of the moderate and Subtropical zone borders. Geographical location, relief, near the Aegean Sea, the openness of the river to the sea, are giving the possibility of presents of three continental zones with: Mediterranean climate, Continental climate and Mountain climate. Variety of eco conditions as well as geographical position are providing relatively wide assortment of agricultural crops to be grown on the territory of Macedonia. Specific characteristics of certain regions give the specific assortment in a certain areas. The most of agricultural area (25% arable land, orchards an number of cattle) has region of Pelagonia. The biggest agricultural area are under vineyards placed in the South Eastern region. The analysis shows that the vegetable is represented mostly in the East Southern region and the region of Skopje. The wheat are represented the most in the region of Pelagonia, while the apple trees are represented with 66,7% in the area of Resen (also in the region of Pelagonia). The last couple of years, except some new types of vegetable crops, in Macedonia has been expanded the production of flowers and take about 30% from total agricultural area in the region of Polog.